Geocultural Orientations of the Second Republic of Lithuania: Ethnic State Promotion Case - Strimaitytė, Dalia (Lietuvos istorijos studijos, 2015)
The article deals with the ethnocentric cultural diplomacy model of the Second Republic of Lithuania, based on President Algirdas Brazauskas’ point of view. The latter model refers to Maironis’ heroic nation-state vision and Šalkauskis’ Eastern and Western cultures synthesis idea: the great power and heroic narrative of Lithuania guaranteed the stability and independence of the statehood, and the cultural synthesis ensured the resistance and flexibility of the identity in relation to other cultures. The cultural diplomacy formed on the national culture and artificially attached to European cultural values promoted the propaganda image of Lithuania hardly reflecting the reality, i.e. it created the vision of an imagined state of tolerance and democracy able to develop an efficient cultural cooperation with other countries by believing that other nations are interested in Lithuania as much as is shown by the vernacular culture.
Keywords: cultural diplomacy; cultural identity; ethnocentrism; national culture; national state